Preparation of Phosphate Liquid and Urea Molasses Minerals Liquid (UMML) As a Precursor of Rumen Biofermentation - Syahrir, Syahriani; Natsir, Asmuddin; Mide, Muhammad Zain; Islamiyati, Rohmiyatul; Asrianie, Ani (Buletin Nutrisi dan Makanan Ternak, 2013)
Urea Molasses Minerals Liquid (UMML) may be a precursor of rumen biofermentation. UMML can provide slow-release nitrogen, minerals and readily available carbohydrate (RAC), but require special studies, especially in determining the type and preparation of constituent materials, especially the provision of water-soluble phosphate minerals. The purpose of this study is to produce a formula of UMML then be used as a precursor of rumen biofermentation. Some of the treatment of super phosphate (SP36) was performed to obtain a preparation method produces dissolved  phosphate  concentrations  are high. Preparation  that  the  highest levels of dissolved phosphate is mixed of super phosphate, organic acids and urea solution, then boiled for 5 minutes. Urea Mineral Molasses liqiud mixed from materials Ca(urea)4Cl2 phosphate solution, saturated NaCl solution and molasses.